Corneal High-Order Aberrations before and after Trans- Epithelial Photorefractive Keratectomy - درويش, . تيم; جلول, قحطان; قاسم, فادي (Latakia University Journal -Medical Sciences Series, 2021)
Objective: To investigate the change of corneal high-order aberrations after transepithelial photorefractive keratectomy on the anterior and posterior corneal urfaces, and to study the relationship of this change with the spherical equivalent of corrected refraction errors. Methods: 50 patients (98 eyes) registered for transepithelial photorefractive keratectomy in the ophthalmic section of Tishreen University Hospital in Lattakia participated in the study and the investigators included the inclusion criteria in the study, where corneal aberration was measured using Sirius Corneal Topography for For 3 and 6 mm pupillary diameter for the anterior and posterior corneal surfaces. measurement repeated 6 months after surgery. Results: For anterior corneal surface, the change of aberrations was not significant at 3 mm pupil diameter, while all aberrations increased at 6 mm pupil diameter (P = 0.005 for total HOAs, P = 0.04 for coma, P = 0.003 for spherical aberration, P = 0.001 for trifoil). For the posterior corneal surface, the aberrations change was not significant at 3 mm pupil diameter, while there was increasing in total HOAs (P = 0.01), coma (P = 0.005), spherical aberrations (P = 0.01) and decreasing trifoil (P = 0.04). We also found that an increase in the spherical equivalent of corrected refractive errors is positively and strongly associated with an increase in total HOAs, coma and spherical aberrations on the anterior surface of the cornea at 6 mm pupil diameter (P = 0.0001 for all), and it is also positively and strongly correlated with an increase in coma and spherical aberrations on the posterior surface of the cornea at 6 mm pupil diameter (P=0.003 and P=0.0001, respectively(. Conclusion: Transepithelial photorefractive keratectomy induces the formation of corneal high order aberrations in the periphery of the cornea and on both anterior and posterior surfaces, and the amount of aberrations is directly correlated with the increase in the spherical equivalent of the corrected refraction errors.